Symmetry or face asymmetry, what is the condition — contemporary opinions of researchers (Journal of Face Aesthetics, 2020)
Symmetry, among others, is the exponent of the correct face structure. 31 publications from the last 5 years were selected from medical databases, which discussed factors that may affect facial symmetry. According to the analyzed reports, the etiology of facial asymmetry is multifactorial through functional, neuromuscular, stomatognathic, environmental, congenital, acquired as a result of injuries, cancer, chronic skin diseases and aging process. Fluctuation asymmetry within the population average does not significantly affect the assessment of facial attractiveness, while a significant degree of fluctuation asymmetry can have a destructive impact on the multi‑faceted quality of life of an individual.
Keywords: facial symmetry; facial asymmetry; influencing factors and symmetry; effects of asymmetry